Pemberdayaan Masyarakat: Upaya Peningkatan Kompetensi Praktisi Kesehatan dalam Analisis Molekuler untuk Diagnosis dan Penatalaksanaan Penyakit: Indonesia - Andini, Ary; Nugraha, Gilang; Hidayat, Muhammad Taufiq; Prayekti, Endah; Salimi, Syafrina Maulidyatus; Navis, Khiliah; Sari, Widya Novita; Fakurazi, Sharida (Jurnal Abdimas Madani dan Lestari (JAMALI), 2025)
Molecular analysis has played a pivotal role in diagnosing and managing diseases during pandemics by enabling early outbreak detection and rapid identification of disease causes, leading to prompt treatment. However, there is still a pressing need to enhance the understanding and proficiency of molecular diagnostics in Southeast Asia. Therefore, proactive measures should be taken to improve comprehension through seminars and training programs focused on molecular analysis. The objective is to strengthen the diagnostic and management capabilities of healthcare workers concerning infectious diseases in Southeast Asia, ultimately aiming to enhance the overall health of the population. The target participants include healthcare professionals, medical laboratory technicians, educators, and students. Through collaboration with Universiti Putra Malaysia, two significant events were organized. The International Seminar on Medical Laboratory Technology (ISoMLatech), took place on July 5, 2023, with the theme "Advancements in Molecular Assay for Diagnosing and Managing Infectious Diseases in Southeast Asia." This event was held in a hybrid format, utilizing Zoom and the UNUSA Auditorium, and it attracted 510. Afterwards, a Short Course was conducted since August 13 to 15, 2023, at Universiti Putra Malaysia (UPM) with 22 participants, The materials received were as followed: the fundamentals of molecular examinations, immunochemical detection, epidemiology of infectious diseases, antimicrobial resistance, and visits to UPM Campus and Institute of Bioscience, UPM. The evaluation results indicate that over 75% of participants rated both ISoMLatech and Short Course as good or very good. Consequently, there is strong anticipation for the continued success and implementation of the program.